Secularism, Religion, and Political Choice in the United States. Issue 4 (23rd April 2013) - Beard, T. Randolph; Ekelund, Robert B.; Ford, George S.; Gaskins, Ben; Tollison, Robert D.
Abstract The effect of religion on political behavior and attachment has been a topic of intense interest in the United States and elsewhere. Less attention has been paid to the issue of secularism. Some analysts have viewed secularism as an absence of religious attachment, and a number of studies have utilized indices of secularization to analyze such topics as economic development or modernization. In this article, we show that secularism, like religion, is in fact a multifaceted category, and should not be viewed as the antithesis of religiosity. Utilizing a very large sample of United States adults, we apply factor analysis to demonstrate that secularism is composed of two logically separate components, and we use these results to examine the role of secularism in political attachments. We suggest that Religious Secularism and Social Secularism are different motivations and have different effects on political behavior and that, politically, the marginal effects of Social Secularism are larger than Religious Secularism in all cases.